Acute haemodynamic and metabolic effects of dopexamine, a new dopaminergic receptor agonist, in patients with chronic heart failure. Issue 3 (September 1985) - Dawson, J R; Thompson, D S; Signy, M; Juul, S M; Turnbull, P; Jenkins, B S; Webb-Peploe, M M
Abstract : Dopexamine, a new compound with postjunctional dopamine receptor activating and beta adrenoceptor agonist properties, was given to 10 patients with chronic heart failure at diagnostic cardiac catheterisation to investigate its acute haemodynamic and metabolic effects. The drug was administered by intravenous infusion in three incremental doses and produced significant dose related increases in cardiac index, stroke volume index, and heart rate and falls in systemic vascular resistance and left ventricular end diastolic pressure; aortic and pulmonary artery pressures were unchanged. Isovolumic phase (max dP/dt and KVmax) and ejection phase (peak aortic blood velocity, maximum acceleration of blood, and maximum rate of change of power with time during ejection) indices of myocardial contractility were all increased by dopexamine but these changes were hard to interpret in the presence of an increase in heart rate. Myocardial efficiency and ejection fraction were both increased and left ventricular end diastolic and end systolic volumes fell. These largely beneficial changes were achieved without a statistically significant increase in myocardial oxygen consumption or disturbance of myocardial metabolic function. Dopexamine was well tolerated but tremor was reported by two patients at the intermediate dose and mild chest pain by two patients at the high dose.